2008
DOI: 10.1007/s10526-008-9180-y
|View full text |Cite
|
Sign up to set email alerts
|

Activity of quinolizidine alkaloids from three Mexican Lupinus against the lepidopteran crop pest Spodoptera frugiperda

Abstract: Bitter lupins (Lupinus spp.) are not used as a protein source because of their toxicity. However, they may have alternative uses as potential sources of natural insecticides. Quinolizidine alkaloids (QA) of three Mexican Lupinus species (Fabaceae): L. montanus (HBK), L. stipulatus (Agardh) and L. aschenbornii (Schauer), were analyzed by capillary Gas Chromatography-Mass Spectrometry. Sparteine was found in high amounts in both L. montanus and L. aschenbornii while the major alkaloids in L. stipulatus extract w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 32 publications
1
34
0
4
Order By: Relevance
“…Several recent studies have identified various potential applications arising from the cultivation and use of plants of the genus Lupinus, including agrochemicals (insecticides) (Bermúdez, Martínez, Figueroa, Legal, & Wink, 2009), food (protein isolates) (Lee et al, 2006) and even medicines (antimicrobial and hypoglycemic drugs) (Dove et al, 2011). In all the cases above, one of the major aims is to achieve a production system that ensures obtaining plants with specific characteristics based on the needs of the final product; for example, increased production of foliage for the extraction of alkaloids and seed production for obtaining protein isolates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have identified various potential applications arising from the cultivation and use of plants of the genus Lupinus, including agrochemicals (insecticides) (Bermúdez, Martínez, Figueroa, Legal, & Wink, 2009), food (protein isolates) (Lee et al, 2006) and even medicines (antimicrobial and hypoglycemic drugs) (Dove et al, 2011). In all the cases above, one of the major aims is to achieve a production system that ensures obtaining plants with specific characteristics based on the needs of the final product; for example, increased production of foliage for the extraction of alkaloids and seed production for obtaining protein isolates.…”
Section: Introductionmentioning
confidence: 99%
“…Dichas aplicaciones pueden ser agroquímicas (insecticidas) (Bermúdez, Martínez, Figueroa, Legal, & Wink, 2009), alimenticias (aislados proteínicos) (Lee et al, 2006) y hasta médicas (antimicrobianas e hipoglucemiantes) (Dove et al, 2011). En cualquiera de los casos, uno de los mayores intereses es lograr una producción que permita asegurar la obtención de plantas con características específicas de acuerdo con las necesidades del producto final; por ejemplo, mayor producción de follaje para la extracción de alcaloides y producción de semilla para la obtención de aislados proteínicos.…”
Section: Introductionunclassified
“…They are used for food and feed (Gladstones, 1974;Dash and Sgarbieri, 1980;López-Bellido and Fuente, 1986;Egaña et al, 1992;Bunger et al, 1999). The wild species also have high protein content, but in contrast to domesticated lupines, their total concentration of quinolizidine alkaloids is greater than 1%; this is their main chemical defense against predators such as insects, herbivores, and omnivores (Bermúdez-Torres et al, 2009). Symptoms of acute toxicity in animals and humans caused by the consumption of wild lupines include diarrhea, vomiting, respiratory failure, and convulsions (Wink and Hartmann, 1981;Agid et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported antiviral, antibacterial, and antifungal properties for these nitrogenated compounds (Wink 2003;Erdemoglu et al 2007;Bermudez-Torres et al 2009). …”
Section: Introductionmentioning
confidence: 99%